UPAYA PENCEGAHAN HIPERTENSI DI DESA PENEGAH KECAMATAN PELAWAN KABUPATEN SAROLANGUN JAMBI - Tina Yuli Fatmawati (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2019)
Hypertension is one of the main problems in public health in Indonesia and the world. It is estimated that around 80% of cases of hypertension occur mainly in developing countries in the year 2025 from a total of 639 million cases in 2000. Problems faced by partners at this time include people in the village of Prevention rarely conducted health counseling by the Puskesmas especially about Hypertension, none Posyandu for the elderly and the community rarely exercise regularly. This community service activity was carried out in the village of Enforcement which is one of the villages located in Pelawan sub-district, Sarolangun District, Jambi. Time of implementation in February 2018. The target is the elderly.The methods used were survey, lecture, discussion, demonstration / simulation approaches. The results of this program is prevention for parents where they are able to understand of the management and prevention of hypertension. It is recommended for Health Officers, especially in Puskesmas, to activate posyandu for the elderly so that the elderly can get health services regularly and get more information about health problems.